2011
DOI: 10.2478/v10011-011-0012-8
|View full text |Cite
|
Sign up to set email alerts
|

Bone Metabolism Markers in Sportswomen with Menstrual Cycle Dysfunctions

Abstract: Kratak sadr`aj: Dobro je poznata ~injenica da su sport ist kinje sa neredovnim menstrualnim ciklusom izlo`ene riziku od smanjenja ko{tane mineralne gustine i posledi~no osteoporozi. Pra}enje nivoa biohemijskih markera ko {tanog metabolizma omogu}ava razumevanje dina m i ~kih promena tokom procesa remodeliranja kosti. Ciljevi spro vedenog istra`ivanja bili su: utvrditi prevalence men stru alnih poreme}aja na uzorku sportistkinja i kontrolne grupe, kao i odrediti nivoe markera ko{tanog metabolizma u grupama ispi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The frequency of all menstrual dysfunctions was greater in groups of athletes in relation to the control group. Primary amenorrhea was determined in 8.33% and oligomenorrhea in 13.09% of female athletes (Ponorac, Rašeta, Radovanović, Matavulj, & Popadić-Gaćeša, 2011) One of the most appropriate mechanisms of menstrual disorders in sports includes also eating disorders. Energy access/availability is defined as the energy calorie intake minus the energy consumed during physical activity.…”
Section: Menstrual Cycle Disordersmentioning
confidence: 99%
“…The frequency of all menstrual dysfunctions was greater in groups of athletes in relation to the control group. Primary amenorrhea was determined in 8.33% and oligomenorrhea in 13.09% of female athletes (Ponorac, Rašeta, Radovanović, Matavulj, & Popadić-Gaćeša, 2011) One of the most appropriate mechanisms of menstrual disorders in sports includes also eating disorders. Energy access/availability is defined as the energy calorie intake minus the energy consumed during physical activity.…”
Section: Menstrual Cycle Disordersmentioning
confidence: 99%
“…In addition, a number of research studies demonstrated the role of vitamin D in blood pressure regulation, autoimmunity, regulation of cell growth and metabolic diseases and malignancy (2)(3)(4)(5)(6)(7)(8)(9). This has all led to increase in vitamin D testing requests, with many laboratories in the United States reporting annual increase rates of 50% or more (10 (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Bone biomarkers and markers of bone changes are the indicators of bone metabolism derived from the bone matrix or bone cells. In making a diagnosis of osteoporosis, in addition to medical history, assessment of the risk factors, clinical examination and certain laboratory tests, the most important is the determination of mass and bone density and the assessment of bone metabolic activity (8,9). The dynamic state of bone metabolism could also provide information about early pathological changes in the bones and the risk of some diseases of the locomotor apparatus.…”
Section: Introductionmentioning
confidence: 99%